Cluster analysis of polyisoprenoid in oil palm (Elaeis guineensis) leaves in different land-uses to find the possible cause of yield gap from planting materials - MOHAMMAD BASYUNI; RIDHA WATI; IRMA DENI; ANANDA RATU TIA; ETTI SARTINA SIREGAR; INDRA SYAHPUTRA (Society for Indonesian Biodiversity, 2018)
Basyuni M, Wati R, Deni I, Tia AR, Slamet B, Siregar ES, Syahputra I. 2018. Cluster analysis of polyisoprenoid in oil palm (Elaeis guineensis) leaves in different land-uses to find the possible cause of yield gap from planting materials. Biodiversitas 19: 1492-1501. The distribution and occurrence of polyprenols and dolichols in the leaves of oil palm (Elaeis guineensis Jacq.) plantations in different land-uses in North Sumatra, Indonesia were analyzed using two-dimensional thin layer chromatography (2D-TLC). Eighty-one of oil palm leaves were sampled to represent twenty-seven sites of land-uses, namely paddy field (four locations), mangrove (three locations) in Lubuk Kertang, Langkat, North Sumatra. In addition, samples from four groups of smallholders in Stabat, Langkat, six sites in Bangun Bandar, Serdang Bedagai, and ten sites on the campus of Universitas Sumatera Utara (USU), North Sumatra were collected. In the leaves, only one type (type II) with respect to the distribution of polyisoprenoids was detected: having the presence of both polyprenols and dolichols. Either type I, having predominance of dolichols over polyprenols or type III, displaying dominating polyprenols over dolichols were not observed. Results also showed that chain-length distribution of ficaprenols (C50-C60) without longer polyprenols (C85-C100) and dolichols of C85-C100 was detected in the paddy field, mangroves, and one site in USU campus. This polyisoprenoid profile was close to dura type of Elaeis guineensis. By contrast, the remaining land-uses had ficaprenols and longer polyprenols, and dolichols (C85-C100), which belong to tenera or pisifera type. To confirm this finding, a dendrogram was constructed. Cluster analysis demonstrated that twenty-seven sites of E. guineensis were grouped into appropriate types of dura, pifiera, and tenera accordingly, indicating that the existence of polyisoprenoids in E. guineensis was a chemotaxonomic marker. The finding of polyisoprenoid pattern of E. guineensis as dura type in mangrove and paddy field sites may reveal significant causes of yield gap in oil palm plantation from planting materials.